Peran Kepemimpinan Suami Dalam Rumah Tangga Perspektif Islam - Rico Setyo Nugroho; M. Dliya’ Ulami’; Soiful Hadi; Dwi Prabowo (SENTRI: Jurnal Riset Ilmiah, 2025)
In Islam, the husband is the leader of the household, so the strong or weak leadership of the husband determines the course of the household. The purpose of this study is to describe the role of a husband's leadership in the household from an Islamic perspective. This research method is qualitative by using case studies. The research data was taken from primary data in the form of interviews with research subjects and secondary data from various references. The data analysis used is a qualitative analysis with the induction method. The result of this study is an understanding of the importance of the husband's leadership role, including as Roisun, Kabirun, Hakimun, and Muaddibun. The stronger the leadership possessed by the husband, the more it will have an impact on the integrity of the household.